PENERAPAN MODEL KOOPERATIF TIPE JIGSAW UNTUK MENINGKATKAN AKTIVITAS BELAJAR SISWA SMP KONSEP SISTEM EKSKRESI MANUSIA - HERNETA FATIRANI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
This study aims to analyze the application of jigsaw-type cooperative learning models to improve student learning activities on the concept of human excretion systems. The subjects in this study were class VIII A students of SMPN 16 Hulu Sungai Tengah, totaling 23 people. Data on student learning activities can be known using observation sheets. The observation sheet contains the teacher's activities and student activities or activities during the continuous teaching and learning process. Data on student activity are analyzed descriptively based on the percent (percentage) scores achieved. The results showed an increase in learning activities which was shown by an increase in student activity in learning at each meeting experienced a significant increase. In the first cycle of meeting 1 the percentage of student activity obtained was 63% with the category